ANALISIS PENGARUH KREDIT USAHA RAKYAT (KUR) BANK RAKYAT INDONESIA TERHADAP PENDAPATAN PETANI CENGKEH DI KABUPATEN SINJAI - Mawarti, Andi; Halil, Abdul; Mudatsir, Rasdiana (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
This study aims to determine the effect of providing People's Business Credit (KUR) by Bank Rakyat Indonesia (BRI) Kanrung Unit, Sinjai Branch on increasing the income of clove farmers in Sinjai Tengah District, Sinjai Regency. The population of this study was taken by simple random or Sample Random Sampling. For the number of samples in this study amounted to 30 respondents. In this study the authors used descriptive quantitative research and the data sources used were primary data and secondary data. The analysis techniques used are validity test, reliability test, simple linear regression and hypothesis testing. The results of this study indicate that the provision of People's Business Credit has a positive and significant effect on increasing community income because the tcount value is obtained at 8.662 and the ttable is 2.048 with a significance level of 0.000. Because the tcount value is greater than the ttable with a significance of less than 0.05 (5%), because the significance level is less than 0.05, the provision of People's Business Credit from Bank Rakyat Indonesia Kanrung Unit, Sinjai Branch has a positive and significant effect on increasing the income of clove farmers in Saotengnga Village, Sinjai Regency.Keywords: Sweet Potato, Variety, Source of Potassium.